Penerapan Sistem Operasional dan Perawatan Pembangkit Listrik Tenaga Bayu di Kelurahan Mangunharjo Kecamatan Tugu - Sahid, Sahid (Kurvamas, 2025)
Gogik Village has the Sumirang tourist area, which, in addition to the natural beauty of the mountains, is very suitable for camping grounds and outbound activities. The obstacle faced in developing the Sumirang tourist area is the lack of an electricity source. As a result, the utilization for camping grounds and outbound activities cannot be implemented yet. This obstacle can be overcome by implementing Micro Hydro Power Plant (PLTMh) technology, as there is micro-hydro potential in this location that can be utilized. To realize this micro-hydro power plant (PLTMh), identification and potential surveys have been conducted at the Sumirang tourist area through community service activities by DIPA Polines in 2017. The output data from the 2017 community service activities will be used as the foundation for the 2019 community service activities. This service aims to implement the design of a Micro Pelton Turbine as the initial driver of an electric generator utilizing the micro-hydro potential in the Semirang tourist area, Gogik village, Semarang regency. The steps to be taken include designing the specifications of the Micro Pelton Turbine based on the results of the study that has been conducted, manufacturing the components, and installing them at the tourist site. In addition, training on operation and maintenance for the operators will also be conducted. The final stage is the implementation of operations, which will be accompanied by the service implementation team. At this stage, performance measurement will be conducted as an evaluation step of the activities. Performance measurement includes the performance of the technology product, by measuring the input and output power of the Micro Hydro Power Plant (PLTMh), and the performance of the operator which includes attitude, knowledge, and skills in operating the PLTMh. The output target of the service is the installation of Micro Pelton Turbine Technology at the location. The Pelton turbine system is suitable for implementation at the tourist site in Gogik village, Semarang regency. The total electrical energy produced is 1,236 Vah and can be used for 3 streetlight points, 1 guard post light point, toilet light, and prayer room.